Post Earthquake Disaster Waste Management In Island Countries: Indonesian Case - Mustainah Mappatoba; Suasa; Muhammad Ahsan Samad; Azlan Abas; Bakri Hasanuddin (Migration Letters, 2023)
This study investigates the challenges and strategies of post-disaster waste management in island countries, with a specific focus on Indonesia, a nation frequently affected by natural disasters. Using the 2018 disaster in Palu, Central Sulawesi as a case study, the research employs quantitative methods to collect data and analyze the issues faced in waste management post-disaster. The study measures waste management options, social considerations, and organizational aspects using a Likert scale, with data collected through questionnaires and document analysis. Regression analysis and structural equation modeling are used to determine relationships between variables. The findings reveal significant impacts of waste management choices and social considerations on organizational aspects. The study underscores the importance of education, awareness, and environmental integration in decision-making, and highlights the role of organizational factors and human resource capacity in effective waste management. The research provides recommendations for government policy and regulation formulation for post-disaster waste management. However, the study’s focus on a specific case study necessitates further research to deepen understanding of earthquake disaster waste management in Indonesia.